PENDIDIKAN KESEHATAN DALAM PENINGKATAN PENGETAHUAN PENDERITA TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS MOPUYA: Health Education in Improving the Knowledge of Patient with Tuberculosis in the Working Area of Mopuya Health Center - Akbar, Hairil; Fauzan, Moh. Rizki; Langingi, Ake Royke Calvin; Darmin (Poltekes Kemenkes Tanjungpinang, 2021)
Many factors affect the recovery of Tuberkulosis patients, namely patient knowledge, patient attitudes towards healing, and patient behavior related to Tuberkulosis patient recovery. Attitude greatly influences one's compliance in taking anti-Tuberkulosis medication because attitude means readiness or willingness to act. Objectives: It is known that the influence of health education about Tuberkulosis on the knowledge of Tuberkulosis sufferers in the work area of ​​Mopuya Health Center Methods: The design of this study used pre-test and post-test. The population in this study were all people who live in the working area of ​​the Mopuya Health Center who were clinically diagnosed by 25 respondents. The sampling technique is saturated sample with a sample of 25 respondents. In this study using the Paired Sample T-Test using a significant level of p value <0.05. Results: It can be seen that the mean value of the difference between the level of knowledge before and after is 0.440 with a standard deviation of 0.507. The results of the Paired Sample T-Test showed p value = 0.000 <0.05, indicating that there was a significant influence between the knowledge of Tuberkulosis patients before and after the provision of health education. Conclusion: That health education has a significant influence on the knowledge of Tuberkulosis sufferers in the working area of ​​Mopuya Health Center.